2021
DOI: 10.1186/s12885-021-09042-6
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of immune cell infiltration and immune-related genes in the tumor microenvironment of osteosarcoma cancer

Abstract: Backgrounds Osteosarcomas are one of the most common primary malignant tumors of bone. It primarily occurs in children and adolescents, with the second highest incidence among people over 50 years old. Although there were immense improvements in the survival of patients with osteosarcoma in the past 30 years, targetable mutations and agents of osteosarcomas still have been generally not satisfactory. Therefore, it is of great importance to further explore the highly specialized immune environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…In addition, our results demonstrated that patients with a lower expression of ZDHHC7/20/21 showed worse survival in LIHC. Liu et al found that the group with lower ZDHHC21 expression levels has higher disease-free survival possibilities than those with high ZDHHC21 in OS [ 67 ]. Thus, these results implied that ZDHHC7/20/21 play oncogenic roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results demonstrated that patients with a lower expression of ZDHHC7/20/21 showed worse survival in LIHC. Liu et al found that the group with lower ZDHHC21 expression levels has higher disease-free survival possibilities than those with high ZDHHC21 in OS [ 67 ]. Thus, these results implied that ZDHHC7/20/21 play oncogenic roles in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ATAD2 is not only tumorigenic but also associated with immune cell infiltration in the tumor microenvironment in osteosarcoma (OS). ATAD2, a downstream target of methyltransferase-like 3 (METTL3), is positively regulated by METTL3 and is a biomarker for predicting prognosis and a candidate target for diagnosis and treatment of OS [ 55 , 130 , 131 , 132 ]. ATAD2 is highly expressed and directly negatively regulated by miR-186 in retinoblastoma (RB).…”
Section: The Role Of Atad2 In Human Malignant Tumorsmentioning
confidence: 99%
“…The immunological environment of the OS consists mainly of T lymphocytes, macrophages, and other cell subpopulations, including B lymphocytes and mast cells. OS cells control the composition and differentiation of immune-infiltrating cells (e.g., the balance between M1 and M2 macrophage subtypes) and create a local immune tolerance environment that promotes tumor growth, MDR, and metastasis [ 9 ]. Tumor-associated macrophages (TAMs) and T lymphocytes are thought to be the main components of the immune environment in OS [ 84 ].…”
Section: Immune Cells Of the Tumor Microenvironment In The Osteosarco...mentioning
confidence: 99%
“…Osteosarcoma (OS) is an extremely aggressive, malignant mesenchymal bone tumor that arises from the malignancy of mesenchymal stem cells (MSCs) [ 4 ]. The formation and development of OS is also associated with immune infiltration and a very complex tumor microenvironment [ 5 , 6 ] OS is a rare tumor type that mainly affects young people and children [ 7 , 8 ], with the incidence of the disease increasing sharply after the age of 50 [ 9 ]. OS most commonly occurs in the distal femur and proximal tibia [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%